RANCANG BANGUN CRM BERBASIS WEB PADA UD. TIMBUL REZEKI - Fahriza Khoirani; Bachtiar Efendi; Muhammad Ardiansyah Sembiring (LPPM STMIK Royal Kisaran, 2023)
Abstrack: UD. Timbul Rezeki, located on Jalan Sei Alim Hasak, Sei Dadap District, Asahan Regency, North Sumatra Province is one of the businesses engaged in the business of selling building materials such as cement, paint, nails, wood and other building materials. In carrying out selling and ordering activities, the goods are still done manually and also not computerized, such as customers buying building materials by coming directly to UD. Rezeki arises or by calling the telephone number of UD. Sustenance arises to place an order for building materials. This makes it difficult for customers to know the quality of the building materials available at UD. Sustenance arises. The purpose of this study is to improve customer service at UD. Sustenance arises by implementing Customer Relationship Management. The method used in this research is to apply the method of Customer Relationship Management (CRM). The results of implementing Customer Relationship Management can improve service to customers at UD. Sustenance arises by providing information about products, account registration, product orders, media comments and product ratings, chats, coupon vouchers, discounts, and product catalogs as product promotion media. Keywords: CRM; Sales; Building Materials; Web. Abstrak: UD. Timbul Rezeki berlokasi Jalan Sei Alim Hasak Kecamatan Sei Dadap, Kabupaten Asahan, Provinsi Sumatera Utara merupakan salah satu usaha bisnis yang bergerak di bidang usaha penjualan material bahan bagunan seperti semen, cat, paku, kayu dan bahan-bahan bangunan lainnya. Dalam melakukan aktivitas menjual dan pemesanan barangnya masih dilakukan secara manual dan juga belum terkomputerisasi seperti pelanggan melakukan pembelian bahan-bahan bangunan dengan datang langsung ke UD. Timbul Rezeki atau dengan menghubungi nomor telepon pihak UD. Timbul Rezeki untuk melakukan pemesanan bahan bagunan. Hal ini yang membuat pelanggan sulit mengetahui kualitas bahan-bahan bangunan yang ada di UD. Timbul Rezeki. Tujuan penelitian ini adalah Untuk meningkatkan pelayanan pelanggan pada UD. Timbul Rezeki dengan menerapkan Customer Relationship Management. Adapun metode yang digunakan dalam penelitian ini adalah dengan menerapkan metode Customer Relationship Management (CRM). Hasil menerapkan menerapkan Customer Relationship Management dapat meningkatkan pelayanan terhadap pelangg:an di UD. Timbul Rezeki dengan memberikan informasi tentang produk, pendaftaran akun, pemesanan produk, media komentar dan rating produk, chatting, voucher kupon, diskon, serta catalog produk sebagai media promosi produk. Kata Kunci : CRM; Penjualan; Material Bahan Bangunan; Web.